Teachers' Challenges in Implementing the Merdeka Curriculum in English Teaching: A Focus on Social Emotional Development: English - indah muslimah nishfu syabani; Aryati Prasetyarini (Prodi Tadris Bahasa Inggris, 2025)
This study explores the strategies and challenges faced by English teachers in implementing the Merdeka Curriculum with a focus on social-emotional development (SED) in junior high schools in Boyolali, Indonesia. Using a qualitative approach through interviews, observations, and document analysis, the research examines how teachers integrate SED into English lessons and how students respond. Teachers employed interactive methods such as group discussions, projects, and games to enhance emotional intelligence and engagement, although they faced challenges related to student motivation, behavior, and classroom constraints. Overall, students responded positively, appreciating the engaging learning atmosphere. The study underscores the need for strong collaboration among teachers, students, and parents to support both academic and social-emotional growth within the Merdeka Curriculum framework.